Coffee rendezvous - Muhammad Nazri, Nurfarah Eryna; Abdul Razak, Fatin Nur Ariena; Sariman, Nurul Afiqah; Hamzah, Nurnatasha Nabila; Zamallh@Zamaleh, Nur Ain Solehah (2020)
Coffee Rendezvous will be set up in Taman Chateau, Ipoh, Perak. The business will be owned by partners who have extensive experiences in their own scope of jobs and they will be taking hands-on management roles in this café. Our targeted customer variety from public officers, above RM 2,500 income earners, long-shift workers and surely the coffee lovers. It is our passion to serve the best range of coffee beverages to our customers along with some sweet desserts as a perfect complement. Across Ipoh, coffee shop business has shown an explosion of support from the locals. As an affluent area with a high locals’ density, our market research has shown that there will be around RM 17,722,600 per year for our market size in this area. While there are currently three businesses offering coffee menus in Ipoh, only two of these fully offer Muslim-friendly servings and none really emphasizing on offering affordable and variety types of coffee beverages for their customers. Thus, our marketing strategies are to serve the best coffee beverages, by using the highest quality ingredients along with offering custom-designed drinks for our customer.